Implementation of Diversion in Juvenile Cases at the Investigation Stage: Perspectives of Restorative Justice and Islamic Criminal Law at the Padangsidimpuan Resort Police - Astria Astuti Annur; Muhammad Arsad Nasution; Nada Putri Rohana (Equality: Law and Social, 2026)
Diversion is a key mechanism in Indonesia's juvenile criminal justice system that promotes restorative justice in resolving cases involving children in conflict with the law. This study examines the implementation of diversion at the investigation stage at the Padangsidimpuan Resort Police, focusing on its procedures, supporting and inhibiting factors, and its relevance to Islamic criminal law. Using a qualitative field research approach, primary data were collected through in-depth interviews with two investigators from the Women and Children Protection Unit (PPA) and the Head of Administrative Affairs of the Criminal Investigation Unit. Secondary data were obtained from legislation, books, and scholarly articles. The findings indicate that diversion has generally been implemented in accordance with Law Number 11 of 2012 through deliberation involving investigators, children, victims, parents, and Community Counselors. However, administrative procedures and post-diversion monitoring remain suboptimal. Key obstacles include victims' reluctance to reconcile, limited public understanding, and insufficient family support. From an Islamic criminal law perspective, diversion aligns with sulh, ta'dib, and maqasid al-shari'ah.